Sosialisasi Kewirausahaan Untuk Meningkatkan Minat Berwirausaha Bagi Guru SDN 09 2x11 Enam Lingkung - Marshal Imar Pratama; Mexano Hans Gery; Nichy Oktaviani; Henny Wati; Sudirman, Sudirman; Anwar Rahim (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service was carried out at SD N 09 2X11 Enam Lingkung where many teachers have not taken advantage of business opportunities, so with this socialization, teachers know the steps in utilizing the environment to do entrepreneurship so that it can improve the economic welfare of the family. The initial step of the speaker will provide tips and tricks on business opportunities, and provide solutions to every problem conveyed by the participants. Entrepreneurship Socialization to Increase Interest in Entrepreneurship for Teachers of SDN 09 2X11 Enam Lingkung” generally went well, this was intended to foster the spirit and motivation of teachers in becoming entrepreneurs. And can increase teachers' insight into becoming successful and competitive entrepreneurs.